Cross‐sectional and longitudinal associations between family meals frequency and children's overweight/obesity in families at high risk of type 2 diabetes: The Feel4Diabetes‐study. Issue 4 (11th January 2023) - Mahmood, Lubna; Gonzalez‐Gil, Esther M.; Makrilakis, Konstantinos; Liatis, Stavros; Schwarz, Peter; Herrmann, Sandra; Willems, Ruben; Cardon, Greet; Latomme, Julie; Rurik, Imre; Radó, Sándorné; Iotova, Violeta; et al.
Summary: Background: The frequency of family meals has been suggested as a protective factor against obesity among children. Objective: This study aimed to investigate the cross‐sectional and longitudinal associations between family meals frequency and children's overweight/obesity in families at high risk of type 2 diabetes (T2D) across six European countries. Methods: 989 parent–child dyads (52% girls and 72% mothers) were included. Participants completed validated measures to assess the frequency of family meals and anthropometrics. Multivariable regression models were applied to examine the longitudinal associations between family meals frequency and overweight/obesity in children. Logistic regression was performed to predict the odds of having overweight/obesity depending on changes in family meals frequency over a two‐year follow‐up period. Analyses were stratified for children's sex. Results: High frequency of family breakfasts and/or dinners was inversely associated with children's BMI in boys and girls at T2. Results showed decreased odds of overweight/obesity at follow‐up among both boys (OR = 0.65; 95% CI 0.41, 0.96) and girls (OR = 0.53; 95% CI 0.31, 0.87) who consumed minimum of three times family breakfasts and/or family dinners a week at baseline. An increase in family breakfasts and/or dinners frequency was associated with lower odds of overweight/obesity in both boys and girls at follow‐up. Conclusion: A high frequency of family breakfasts and/or dinners but not lunch during childhood is associated with lower odds of overweight/obesity development in children from families at high risk of T2D. The promotion of family meals could help in preventing the development of overweight/obesity among children.